Neurosyphilis: An Unresolved Case of Meningitis - Shagufta Ahsan; Joesph Burrascano (Case Reports in Infectious Diseases)
Neurosyphilis can cause both symptomatic and asymptomatic meningitis. However the epidemiology of modern neurosyphilis is not well defined because of the paucity of population-based data. The majority of neurosyphilis cases have been reported in HIV-infected patients. Here we present a case of early neurosyphilis/symptomatic syphilitic meningitis in a non-HIV patient who presented with rash but was mistakenly treated for early latent or secondary syphilis. Syphilis presenting with a skin rash and an extremely high RPR titer could indicate CNS infection rather than simply secondary syphilis because rash is a nonspecific manifestation of disseminated infection. Given the effectiveness of penicillin therapy, why is the rate of syphilis continuing to increase? Is it due to a failure of prevention or could it be also because of failure to diagnose and treat syphilis adequately, as in this case?